2021
DOI: 10.3390/su13126799
|View full text |Cite
|
Sign up to set email alerts
|

CFD Investigation of Vehicle’s Ventilation Systems and Analysis of ACH in Typical Airplanes, Cars, and Buses

Abstract: The simulation of the ventilation and the heating, ventilation, and air conditioning (HVAC) systems of vehicles could be used in the energy demand management of vehicles besides improving the air quality inside their cabins. Moreover, traveling by public transport during a pandemic is a concerning factor, and analysis of the vehicle’s cabin environments could demonstrate how to decrease the risk and create a safer journey for passengers. Therefore, this article presents airflow analysis, air changes per hour (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 61 publications
0
21
0
Order By: Relevance
“…All the ventilation modes were tested considering outside air intake provided by a HVAC system, which is with no air recirculation; the windows were considered closed for the entire duration of the journey. Different HVAC flow rates (from 10% to 100% of the maximum flow rate), Q (m 3 h −1 ), were investigated: in particular, the intermediate airflow rate (flow rate at the 50% of the maximum fan capacity, hereinafter referred as Q 50% ) is set at 216 m 3 h −1 on the basis of the value adopted by Pirouz et al in their study 49 ; this value is consistent with the intermediate fan capacity reported by Ullrich et al 50 for a real car whose internal volume is comparable to that of the cabin model employed for the scenarios under study. We point out that the flow rate also affects the velocity ( u ) at the inlet sections and then the velocity field in the car cabin; moreover, in the simulations here performed a single angle of inlet air‐flow rate was adopted.…”
Section: Methodsmentioning
confidence: 99%
“…All the ventilation modes were tested considering outside air intake provided by a HVAC system, which is with no air recirculation; the windows were considered closed for the entire duration of the journey. Different HVAC flow rates (from 10% to 100% of the maximum flow rate), Q (m 3 h −1 ), were investigated: in particular, the intermediate airflow rate (flow rate at the 50% of the maximum fan capacity, hereinafter referred as Q 50% ) is set at 216 m 3 h −1 on the basis of the value adopted by Pirouz et al in their study 49 ; this value is consistent with the intermediate fan capacity reported by Ullrich et al 50 for a real car whose internal volume is comparable to that of the cabin model employed for the scenarios under study. We point out that the flow rate also affects the velocity ( u ) at the inlet sections and then the velocity field in the car cabin; moreover, in the simulations here performed a single angle of inlet air‐flow rate was adopted.…”
Section: Methodsmentioning
confidence: 99%
“…The continuous development of computational fluid dynamics (CFD) theory and the associated simulation tools and the rapidly growing computing power have made it much easier than ever to analyse complex flow problems in various engineering applications. ANSYS Fluent is one of the most frequently-used CFD software, and it is also the main simulation platform for the aforementioned studies (Ibrahim and Mehta, 2018;Pirouz et al, 2021;Kale et al, 2007). ANSYS Fluent provides comprehensive modelling capacities for a wide range of incompressible and compressible, laminar and turbulent fluid flow problems, and more technical information can be found in its official user's guide.…”
Section: Model Set-upmentioning
confidence: 99%
“…Ventilation and ambient loads are functions of the temperature difference between the cabin and the ambient load. The air flow rate for the buses depends on the operating of the air conditioning system, with values between the 0.05 m 3 /s and 0.3 m 3 /s [28]. For the city buses with frequently stops, the fresh air supplied by ventilation is dominated by the air flow through the open doors, and the ventilation can be used for the lower value, which is 0.05 m 3 /s [28].…”
Section: Q Venmentioning
confidence: 99%
“…The air flow rate for the buses depends on the operating of the air conditioning system, with values between the 0.05 m 3 /s and 0.3 m 3 /s [28]. For the city buses with frequently stops, the fresh air supplied by ventilation is dominated by the air flow through the open doors, and the ventilation can be used for the lower value, which is 0.05 m 3 /s [28]. Heat transfer due to the ventilation can be estimated with Formula (8) and depends on the temperature difference (∆T), the specific heat, the air density (ρ air ) and the air flow rate ( .…”
Section: Q Venmentioning
confidence: 99%